Comunicación, Desarrollo y Cambio Social en la oferta académica universitaria de pregrado en América Latina: Rafael Ángel Salazar Martínez y Rayza Portal Moreno - Salazar Martínez, Rafael Ángel; Portal Moreno, Rayza (Quórum Académico, 2021)
This paper analizes the undergraduate academic offerings of the bestpositioned universities in each country, out of the 20 make up thearea. Methodologically, the selection was based on the triangulationof information contained in three of the most internationally renownedclassifiers. The profiles and curricular net of 52 Communication andJournalism courses were examined, 16 of which are concentratedin the Development and Social Change (CDSC). In each case, theirrepresentativeness was determined. Four main thematic areas wereidentified, where it can be seen there is a curricular dispersion, as wellas some gap and disagreements with the most current trends in scientificproduction. We conclude, however, the empirical evidence offers asatisfactory overview, with a generalized offer whose weight in trainingis significant.